2021
DOI: 10.1002/gj.4290
|View full text |Cite
|
Sign up to set email alerts
|

Recent felt earthquakes (Mw 5.0–5.9) in Mizoram of north‐east India region: Seismotectonics and precursor appraisal

Abstract: Eight medium magnitude (Mw 5.0-5.9) severely felt earthquakes, mostly at a shallower depth (<35 km), occurred in a short period of 7 months only, April-October, 2020, in Mizoram State, north-east region (NER) of India, and it created much panic in the state. The increasing population growth as well as rapid urbanization in Aizawl, the capital city of Mizoram, may be under severe threat for an impending large earthquake in the region. The NER, India, is jawed between two arcs, the Himalayan Arc collision zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…The 28 April 2021 foredeep earthquake Mw 6.1 occurred at the northern end of the Kopili Fault in the Assam valley (Figure 3), and it caused severe shaking, damage to the weak structures, ground liquefaction, fractures, and so on resulting in maximum intensity VII within a radius of 50 km (Dey et al, 2022). The GCMT solution with a centroid depth at 39 km shows strike‐slip faulting, and the NW trending northeast dipping nodal plane is conformable with the Kopili Fault (Figure 3; Hazarika & Kayal, 2022) inferred this event to the Kopili Fault, that occurred by right‐lateral strike‐slip movement.…”
Section: Recent Strong Earthquakes In the Eastern Himalayasmentioning
confidence: 82%
See 1 more Smart Citation
“…The 28 April 2021 foredeep earthquake Mw 6.1 occurred at the northern end of the Kopili Fault in the Assam valley (Figure 3), and it caused severe shaking, damage to the weak structures, ground liquefaction, fractures, and so on resulting in maximum intensity VII within a radius of 50 km (Dey et al, 2022). The GCMT solution with a centroid depth at 39 km shows strike‐slip faulting, and the NW trending northeast dipping nodal plane is conformable with the Kopili Fault (Figure 3; Hazarika & Kayal, 2022) inferred this event to the Kopili Fault, that occurred by right‐lateral strike‐slip movement.…”
Section: Recent Strong Earthquakes In the Eastern Himalayasmentioning
confidence: 82%
“…The recent seismicity recorded by the local network shows intense bimodal seismic activity along the Kopili Fault; the earthquakes are intense in the upper crust at a shallower depth (0–20 km) as well as in the lower crust and crust–mantle boundary at a deeper depth (30–50 km), the middle crust remaining less active (Kayal et al, 2012). The 2016 earthquake Mw 6.7 in Imphal (Manipur) is inferred to have occurred by strike‐slip faulting at the southernmost end of the Kopili Fault at a deeper depth (40 km) where it intersects the thrust system in the Indo‐Burma Arc (Hazarika & Kayal, 2022; Figure 3).…”
Section: Recent Strong Earthquakes In the Eastern Himalayasmentioning
confidence: 99%
“…Vorobieva et al (2021) very recently, using the Block-and-Fault Dynamics model, showed that the India-Burma megathrust is locked and can generate an M8+ event in the area. Similarly, Hazarika and Kayal, (2022), postulated that the IBW is accommodating a part of the plate movement by strike-slip motion along the plate boundary causing shallower earthquakes in Mizoram and suggested that this could be a precursor for an impending large earthquake in the magnitude range M w ~7.0 in the IBW, which is not unusual in the subduction zone as observed in the past (Gupta and Singh, 1989). Vorobieva et al (2021) further inferred that aseismic slip in the CMF significantly reduces the seismic hazard of great interplate earthquakes in the region and CMF almost does not contribute to regional shortening.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining motion might be accommodated between India and Sunda plates (Hazarika and Kayal, 2022). Mallick et al (2019) argued that the India and Burma plates are fully coupled up to a depth of ~30 km and the active convergence across the IBR is going on at a rate of ~12-24 mm/year.…”
Section: Discussionmentioning
confidence: 99%
“…The complicated tectonics of the region produced two great earthquakes, the 1897 Shillong Plateau earthquake (Mw 8.4) and the 1950 Assam earthquake (Mw 8.6) (Ambraseys & Douglas, 2004; Ben‐Menahem, Aboodi, & Schild, 1974; Tillotson, 1951). Besides these great earthquakes, the region witnessed a total of 25 large earthquakes (Mw ≥ 7.0) in the past, since 1869 (Hazarika & Kayal, 2022; Kayal, 2008; Nandy, 2001). The great and large earthquakes are mostly due to the collision tectonics in the north and subduction tectonics in the east (Copley & McKenzie, 2007; Gahalaut et al, 2013; Gahalaut & Kundu, 2016; Kayal, 2008; Kumar, Mitra, & Suresh, 2015; Satyabala, 2003).…”
Section: Introductionmentioning
confidence: 99%